Personality Traits dan Dukungan Sosial sebagai Prediktor Service Orientation Tenaga Kesehatan - Fadhilah Ahmad Qaniah; Vifi Nurwianti (Jurnal Manajemen Kesehatan Indonesia, 2021)
Personality traits are one of the intrapersonal factors that makes health workers differently doing quality of service orientation. As well as social support from family, friends, and significant others are one of interpersonal factor that assumedly can increase the desire of health workers to serve people better. This research aims to see the influence of personality traits and social support for service orientation of health worker during the Covid-19 pandemic. This research uses quantitative methods with linear regression analysis. Participants were 218 health workers who are active with various professions/jobs according definition of health workers in UU number 36 of 2014. The results show that the effectiveness of personality traits model (R2 adjusted = 0,309) and also the quality of social support (R2 adjusted = 0,166) can significantly predict (p < 0,01) service orientation. Personality traits especially agreeableness traits and conscientiousness traits were shown to be predictors. As well social support, especially from the significant other dimension has been proven to be a predictor. Thus, to improve service orientation, it is necessary to improve the quality of personality traits and social support received.